Christian Clergy in American Politics - Olson, Laura R., 1967-; Crawford, Sue E. S., 1967- (Book collections on Project MUSE., 2001)
"In this book Sue E.S. Crawford, Laura R. Olson, and their coauthors explore the political choices clergy make and the consequences of these choices. Drawing on personal interviews and statistical data to place the actions of clergy in both their religious and secular contexts, the authors study mainline and evangelical Protestant, Catholic, and Mennonite communities. They examine the role of white, African American, and female religious leaders. And they address issues of local development, city government, and national and international politics."--Jacket.